Analysis of the Islamic Philanthropic A Quantitative Study of Aid Clusters in Jambi - Armaz Hardi, Eja; Agustin Nengsih, Titin; Rosmanidar, Elyanti (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This study examines the model of Islamic philanthropic donors in Jambi Province using a quantitative approach involving cluster analysis and Structural Equation Modeling (SEM). This study is important given the strategic role of Islamic philanthropy in the economic and social empowerment of communities, yet understanding of donor behavior remains limited. The research aims to map donor segmentation and identify the main factors influencing donation behavior, including aspects of spirituality, trust, and empathy. Data was collected from donors of Islamic philanthropic institutions in Jambi using a representative sample. The results show that donor segmentation is dominated by those over 40 years of age and with a high school education, spanning various professions. SEM confirmed a valid and reliable model with R-square values ranging from 0.246 to 0.497. Path analysis revealed spirituality, trust, and empathy as significant drivers of donations, while knowledge and wealth did not have a direct impact. The study emphasizes the importance of transparent fund management, strengthening zakat literacy, and digital technology innovation to enhance donor trust and loyalty, as well as the effectiveness of Islamic philanthropic institutions in Jambi